The Acquisition of Subject-Verb Agreement Among Norwegian (Teenage) Learners of English: Focus on the Subject - Kristin Killie (Journal of Linguistics and Language Teaching)
Subject-verb agreement in English is a complex area that causes problems for learners. It is important to determine which aspects of this topic are most difficult to learn and automatize so that we can focus on these in the language classroom. The present paper aims to make a contribution by presenting data on subject-verb agreement among Norwegian adolescents (12-13 and 15–16 years old). The research question is whether learners make more mistakes with some types of subject than with others. A main finding is that there are more errors with noun subjects than with personal pronoun subjects. It is argued that this is the result of drilling of paradigms as well as high frequencies in the input and output. Another finding is that the error rate is particularly high when the subject consists of two or more conjoined noun phrases. This fact is explained in terms of ‘Agreement Attraction’ (Strang 1966). On the basis of the data, it is suggested that the teaching of subject-verb agreement should focus more on noun subjects, including conjoined subject noun phrases.